Short Term Outcome of Double Valve Replacement vs. Aortic Valve Replacement with Mitral Valve Repair in Bangladesh: A Comparison (Cardiovascular Journal, 2021)
Background: Although all mitral valves are not repairable, most non rheumatic valves and a substantial proportion of rheumatic valves are amenable to repair. Repair preserves the normal valvular tissue, so the left ventricular function is well maintained post-operatively. Combined aortic and mitral valve surgery is associated with increased mortality and morbidity. Several studies have shown the superiority of DVR (Double valve replacement) in this entity to prevent reoperation. Some other data suggested superiority of aortic valve replacement combined with mitral valve repair in double valve disease. No study had been done over Bangladeshi population. Our aim was to compare the short-term outcome of mitral valve repair and aortic valve replacement with double valve replacement.Methods: It was a prospective non-randomized observational study took place in the Department of Cardiac Surgery of National Institute of Cardiovascular Disease. In this study post-operative result of double valve replacement was compared with aortic valve replacement and mitral valve repair. Total 60 patients under went aortic valve replacement with either mitral valve replacement (n=30) marked as group A or (n=30) repair marked as Group B.Results: Aortic cross clamp time and cardiopulmonary bypass time was higher in group B than group A but it was well tolerated without any short-term measurable consequences. Required inotrope support was 49.8±2.3 hours in group B and 87.2±3.5 hours in group A (p